SINTESIS DAN AKTIVITAS ANTIOKSIDAN PENANGKAPAN RADIKAL BEBAS DPPH SENYAWA 2,2',4-TRIHIDROKSI-4'- METOKSIKALKON - , Navista Sri Octa U. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The presence of an excess of free radicals can stimulate oxidative stress in the body. This condition will cause various diseases such as cancer, inflammation, and cardiovascular disease. The activity of free radicals can be inhibited by antioxidants and one class of compounds having that activity is chlalcone. This study aimed to synthesize and determine the antioxidant activity of compounds 2,2',4-trihydroxy-4'-methoxychalcone. Synthesis was done by reacting 2-hydroxy-4-methoxyacetophenone and 2,4-dihydroxybenzaldehide using conventional and microwave irradiation (MWI) methods with alkaline and acid catalysts. The rendement of the compound derived from each method was calculated. The purity of synthesis product was evaluated using thin-layer chromatography and melting point measurement. The structure of the compound was determined using spectroscopic methods, included IR , UV-Vis, mass, 1 H- and 13 C-NMR and also 2D-NMR (COSY, HMQC, and HMBC). Investigation of the antioxidant activity of 2,2',4-trihydroxy-4'-methoxychalcone was carried out by the DPPH radical scavenging method with quercetin was used as positive control. The result showed that 2,2',4-trihydroxy-4'-methoxychalcone can be synthesized by conventional and MWI methods using acid catalyst to yield of 1.11% and 1.2%, respectively. This compound had IC 50 86,64 Î¼g/ml, showed that DPPH radical scavenging activity was lower than quercetin with IC 50 of 3.783 Â± 0.090 Î¼g/ml.